Efficacy of a Travelers' Diarrhea Vaccine System in Travelers to India. Issue 6 (26th August 2013) - Steffen, Robert; Cramer, Jakob P.; Burchard, Gerd; Jelinek, Tomas; Schwarz, Ute; Ramdas, Prabhugaunker; Chatterjee, Santanu; Jiang, Zhi‐Dong; DuPont, Herbert L.; Dewasthaly, Shailesh; Westritschnig, Kerstin; Behrens, Ronald H.
Abstract : Background: A patch vaccine containing heat‐labile toxin (LT) from enterotoxigenic Escherichia coli (ETEC) has demonstrated to be beneficial in reducing the rate and severity of travelers' diarrhea in Latin America. To evaluate the efficacy of this transdermal vaccine system in an area with a different diarrheal pathogen profile, an additional phase 2 study was conducted in European travelers to India. Methods: For this multicenter, randomized, double‐blinded, placebo‐controlled field study 723 subjects were recruited; 603 (299 LT vaccine, 304 placebo) were included in the per‐protocol‐population (PPP). Results: Although the LT patch induced a measurable LT immune response in recipients, it failed to protect against LT ETEC or all‐cause diarrhea. In the PPP the incidence rate of diarrhea as per primary endpoint was 6.0% (18 of 299) in the vaccine group and 5.9% (18 of 304) in the placebo group. Additionally, lower than expected rates of LT ETEC diarrheas were observed in India. The vaccine delivery system frequently produced rash and pruritus at the site of application, long term hyperpigmentation persisted in a minority of LT recipients, and also few site reactions were noted in the placebo group. Conclusions: The evaluated patch vaccine failed to satisfy mainly with respect to protective efficacy. Noninvasive prophylactic agents against travelers' diarrhea, particularly vaccines against the most frequent pathogens, thus continue to be badly needed.